2014
DOI: 10.4062/biomolther.2014.065
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-Derived Stem Cells Improve Efficacy of Melanocyte Transplantation in Animal Skin

Abstract: Vitiligo is a pigmentary disorder induced by a loss of melanocytes. In addition to replacement of pure melanocytes, cocultures of melanocytes with keratinocytes have been used to improve the repigmentation outcome in vitiligo treatment. We previously identified by in vitro studies, that adipose-derived stem cells (ADSCs) could be a potential substitute for keratinocytes in cocultures with melanocytes. In this study, the efficacy of pigmentation including durability of grafted melanocytes and short-term safety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 18 publications
0
19
0
2
Order By: Relevance
“…Unfortunately this study hasn't been done before on human but similar study was done on skin animals, in a study made by Lim et al [20] on lab animals showed that, Grafting of melanocytes co cultured with ADSCs increased melanocyte number in nude mice compared to melanocyte monocultures.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately this study hasn't been done before on human but similar study was done on skin animals, in a study made by Lim et al [20] on lab animals showed that, Grafting of melanocytes co cultured with ADSCs increased melanocyte number in nude mice compared to melanocyte monocultures.…”
Section: Discussionmentioning
confidence: 99%
“…Repigmentation of vitiligo depends on available melanocytes from three possible sources: from the hair follicle unit which is the main provider of pigment cells, from the border of vitiligo lesions, and from unaffected melanocytes within depigmented areas [ 32 ]. Melanocytes rarely undergo mitosis without growth factors; therefore, mitogenic factors are used in transplantation treatments for this disease [ 33 , 34 ]. Repigmentation occurs due to the migration of melanocyte stem cells (MelSCs) located in the lower part of the hair follicle (infundibulum).…”
Section: Vitiligomentioning
confidence: 99%
“…Repigmentation occurs due to the migration of melanocyte stem cells (MelSCs) located in the lower part of the hair follicle (infundibulum). Therefore, this process starts perifolliculary [ 33 36 ].…”
Section: Vitiligomentioning
confidence: 99%
“…Pigmentacja zaczyna pojawiać się pomiędzy 4. a 5. tygodniem i trwa do 6 miesięcy, a nawet dłużej [32]. Ponieważ melanocyty rzadko podlegają mitozie bez pomocy czynników wzrostu lub czynników mitogennych, efekty podawania samych melanocytów w plamy bielacze były słabsze niż w przypadku podawania ich z komórkami naskórka w formie przeszczepów [34,35].…”
Section: Bielactwounclassified
“…Stwierdzono lepsze efekty jednoczesnego podawania melanocytów i ADSCs, które hoduje się oddzielnie i miesza się w proporcji 1 : 1, 1 : 2 lub 1 : 3 w porównaniu z podawaniem tylko czystych melanocytów [34].…”
Section: Bielactwounclassified